Perancangan dan Implementasi Sistem Inventory Berbasis Desktop Menggunakan Model Waterfall pada CV. Permata Printing - Abdul Hamdani Eko Saputro; Bagas Mishbahuddin; Bayu Santoso; Maulana Ardhiansyah (CV. Shofanah Media Berkah, 2026)
This research aims to design and implement a desktop-based inventory information system at CV. Permata Printing to address the problem of non-computerized inventory management. Currently, the inventory data collection process at CV. Permata Printing is still done manually, resulting in a high risk of data loss, discrepancies between the physical quantity of goods and records, and difficulties in monitoring stock availability in real-time when there is a surge in orders. The development of this system uses the Waterfall model which includes the stages of analysis, design, coding, testing, and maintenance, by implementing the Java programming language. The result of this research is a desktop inventory application that is able to integrate inventory data systematically. The implementation of this system has been proven to increase the accuracy of inventory data collection, minimize calculation errors, and make it easier for employees to monitor inventory more quickly and efficiently compared to previous conventional methods.